Synthesis of heterogeneous materials for cooling applications - Choy, Wei Li (2017)
Our world’s natural resources are finite and dwindling at an alarming rate, causing a great environmental concern. With the rise of industries and standard of living, there is constant and increasing demand for new environmental sustainable resources and energy efficient technology. Research and experiments are done to investigate the thermophysical properties and adsorption characteristics of six potential Metal Organic Frameworks for storage and cooling applications in this project. MIL-101(Cr), MOF801SC, Aluminium Fumarate, Aluminium Fumarate (Formic), HKUST-1 and CAU-10 were synthesised and experimented with water for adsorption at temperatures ranging from 298K to 333K. Brunauer-Emmett-Teller method was used to analyse the morphology, including: average pore width, pore volume and pore surface area, of the synthesised samples. Density Functional Theory model was used to investigate pore size distribution. Scanning Electron Microscopy was used to provide spatial images of the microporous structures. It was found that MIL- 101(Cr) has the largest pore size of 23 Å, largest total pore volume of 1.409 cc/g and largest specific surface area of 3060.49 m2/g among the six synthesised samples. Aluminium Fumarate has the highest maximum N2 sorption/desorption uptake of 1175.78 cm3 at 273K. Thermo-Gravimetric Analyser was employed to investigate the water adsorption capabilities of the synthesised samples for working temperatures ranging from 298K to 333K, with pressures ranging from the Henry’s region to the saturated conditions. Results obtained were fitted with Chakraborty-Sun isotherm equation. From the experimental results, it can be concluded that the lower temperatures provide higher uptake at low pressure and higher temperature attain higher uptake at high pressure. Higher working temperatures attain adsorption equilibrium faster than lower working temperatures. Isosteric heat of adsorption graphical plots showed that as the uptake increases, isosteric heat of adsorption either gradually decreases due to the decrease in available pores for adsorption, or increases steadily after overcoming hydrophobic nature at Henry’s region.